RIGHTS OF MATERIAL TEST ON GOVERNMENT REGULATION IN LIEU OF LAW IMPLEMENTATION - Sulistyani Eka Lestari (Fakultas Hukum, Universitas Maarif Hasyim Latif, 2018)
A test on a law conducted by the Constitutional Court is not only always related to the substance of a law but it can also associate with the formation process of the law. This means that Constitutional Court tests a law both materially and formally. Testing on other regulations under legislation such as government regulation, Regulation of the President, and others carried out by the Supreme Court based on the Supreme Court Regulation Number 1 of 1999 on the Material Testing lawsuit. Especially on Government Regulation in Lieu of Law (Government Regulation), cannot be tested either by the Supreme Court and the Constitutional Court as it is temporary. The tests are carried out by non-justicial institution that their title depen on the institution that has the authority to conduct such testing. . This study uses the methodology of normative juridical deduction, the judicial approach. At the end of the discussion will be found the answer from the legal issues that the law of the State Administrai important role in the prevention and eradication of corruption. With prescriptions for a legal solution